The emotionally healthy church : a strategy for discipleship that actually changes lives - Scazzero, Peter, 1956-; Bird, Warren (Grand Rapids, Mich. : Zondervan, 2003)
Discusses how to become a vessel of change within one's church and argues that one must become emotionally mature in order to achieve true spiritual maturity
Part 1. Discipleship's missing link. As go the leaders, so goes the church ; Something is desperately wrong -- Part 2. Biblical basis for a new paradigm of discipleship. Discipleship's next frontier -- emotional health ; Inventory of spiritual/emotional maturity -- Part 3. Six principles of an emotionally healthy church. Principle 1 : look beneath the surface ; Principle 2 : break the power of the past ; Principle 3 : live in brokenness and vulnerability ; Principle 4 : receive the gift of limits ; Principle 5 : embrace grieving and loss ; Principle 6 : make incarnation your model for loving well -- Part 4. Where we go from here. Next steps into the new frontier of discipleship ; Discussion guide for restructuring discipleship
Includes bibliographical references (pages 219-221)
Keywords: Emotional maturity -- Religious aspects -- Christianity; Discipling (Christianity)